SOSIALISASI DAN EDUKASI LEMBAGA PEMBIAYAAN SYARIAH BAGI PENGURUS MASJID KEMENTERIAN/LEMBAGA DAN BUMN - Kusumastuti, Retno Dyah; Faizi; Kusuma, Airlangga Surya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ABSTRACT Indonesia, where the majority of the population is Muslim, has great potential to become a center for the development of Islamic finance, including Islamic financing institutions. However, the development of Islamic financing institutions themselves is still relatively small. One of the problems hindering the development of Islamic financing institutions is the low level of public Islamic financial literacy. In addition, the community also still considers Islamic financing institutions to be the same as conventional financing institutions. Therefore, it is necessary to conduct training to improve the understanding of Islamic financing institutions in the community. To be more effective, the training should be aimed at those who have influence in society, such as mosque administrators. It is hoped that with this training, the understanding of mosque administrators regarding Islamic financing institutions can increase, and mosque administrators can pass on knowledge about Islamic financing institutions to the wider community. To carry out the training, the UPN Veterans Jakarta service team then collaborated with the Forum for Mosque Administrators of Ministries/Agencies and State-Owned Enterprises to hold socialization of Islamic financing institutions for mosque administrators. This service activity method uses the lecture method as a method for socializing Islamic financing institutions, which is then followed by a question and answer session. In the future, it is hoped that mosque administrators will be able to pass on knowledge about Islamic financing institutions to the wider community so that understanding of Islamic financing institutions in the community will also increase. ABSTRAK Indonesia yang mayoritas penduduknya beragama Islam memiliki potensi yang besar menjadi pusat pengembangan keuangan syariah, termasuk lembaga pembiayaan syariah. Namun perkembangan lembaga pembiayaan syariah sendiri masih relatif kecil. Salah satu permasalahan yang menghambat perkembangan lembaga pembiayaan syariah adalah rendahnya tingkat literasi keuangan syariah masyarakat. Selain itu masyarakat juga masih menganggap lembaga pembiayaan syariah sama dengan lembaga pembiayaan konvensional. Oleh karena itu, perlu dilakukan pelatihan untuk meningkatkan pemahaman lembaga pembiayaan syariah di masyarakat. Agar lebih efektif, pelatihan tersebut sebaiknya ditujukan ke pihak-pihak yang memiliki pengaruh di masyarakat, seperti pengurus masjid. Diharapkan dengan pelatihan tersebut, pemahaman pengurus masjid terkait lembaga pembiayaan syariah dapat meningkat, dan pengurus masjid dapat meneruskan pengetahuan mengenai lembaga pembiayaan syariah ke masyarakat luas. Untuk melaksanakan pelatihan tersebut, tim pengabdian UPN Veteran Jakarta selanjutnya bekerjasama dengan Forum Silaturrahim Takmir Masjid Kementerian/Lembaga dan BUMN untuk mengadakan sosialisasi lembaga pembiayaan syariah bagi pengurus masjid. Metode kegiatan pengabdian ini menggunakan metode ceramah sebagai metode untuk sosialisasi lembaga pembiayaan syariah, yang selanjutnya dilanjutkan dengan sesi tanya jawab. Kedepannya diharapkan pengurus masjid dapat meneruskan pengetahuan mengenai lembaga pembiayaan syariah ke masyarakat luas, sehingga pemahaman mengenai lembaga pembiayaan syariah di masyarakat juga meningkat.